Development of a Scale to Assess Kerala Farmers’ Attitude towards Digital Technologies in Agriculture - S. Shanila; S. HELEN (Indian Journal of Extension Education, 2025)
The expanding role of digital technologies in agriculture highlights the importance of understanding farmers’ attitudes toward their adoption, particularly in the context of Kerala’s digital infrastructure and e-governance. The research, carried out in 2025, sought to create a standardized Likert attitude scale to evaluate the attitude of Kerala farmers on the employment of digital technologies in agriculture. A preliminary collection of 68 attitude statements was formed through literature research and expert input. These statements were assessed by 30 specialists in agricultural extension, and following their feedback, 56 items were chosen for further analysis. The chosen items were distributed to 60 farmers from non-sample regions—30 from Karuvatta Panchayat and 30 from Kayamkulam Municipality, situated in the Onattukara Sandy Plain agro-ecological unit. Participants rated the statements using a five-point Likert scale. Employing the t-test established by Edwards (1957, 1969), statements with strong discriminative ability were retained, resulting in a final scale of 20 items comprising 10 positive and 10 negative statements, achieving a Cronbach’s Alpha of 0.91, which demonstrates excellent reliability and content validity confirmed through expert assessment.